2023
DOI: 10.1371/journal.pone.0269104
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and SARS-CoV-2 invasion in general populations: A scoping review over the first year of the pandemic

Abstract: Since the beginning of the COVID-19 pandemic, counting infected people has underestimated asymptomatic cases. This literature scoping review assessed the seroprevalence progression in general populations worldwide over the first year of the pandemic. Seroprevalence studies were searched in PubMed, Web of Science and medRxiv databases up to early April 2021. Inclusion criteria were a general population of all ages or blood donors as a proxy. All articles were screened for the title and abstract by two readers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…This review covers prevalence estimates from 50 countries or regions from January 2020 to March 2022, but prevalence in these areas only represent a small part of the COVID-19 infection and vaccination among older adults in the world. Along with other reviews 63,64 , this scoping review shows that prevalence and seroprevalence studies were concentrated in several high-resource countries or areas such as the United States and Europe. Although our search included most of 2022, most included studies were conducted in 2020 and 2021; this may have reflected an urgent need to obtain prevalence estimates early on in the pandemic as well as the time it takes for the publishing process.…”
Section: Discussionmentioning
confidence: 93%
“…This review covers prevalence estimates from 50 countries or regions from January 2020 to March 2022, but prevalence in these areas only represent a small part of the COVID-19 infection and vaccination among older adults in the world. Along with other reviews 63,64 , this scoping review shows that prevalence and seroprevalence studies were concentrated in several high-resource countries or areas such as the United States and Europe. Although our search included most of 2022, most included studies were conducted in 2020 and 2021; this may have reflected an urgent need to obtain prevalence estimates early on in the pandemic as well as the time it takes for the publishing process.…”
Section: Discussionmentioning
confidence: 93%
“…The data included: (1) age, gender, comorbidities (hypertension, diabetes mellitus, chronic heart failure, chronic kidney disease, previous myocardial infarction, previous stroke, chronic obstructive pulmonary disease [COPD], chronic liver diseases, solid tumors, onco-hematological diseases, and being bedridden), home-therapy drugs; (2) the department from which the patient was transferred to the internal medicine department; (3) We considered the high/low cut-off of NT-proBNP, procalcitonin, AST, ALT and hs-CRP according to upper laboratory limits as follows: NT-proBNP, 260 pg/mL; procalcitonin, 0.5 µg/L; AST, 34 UI/L; ALT, 55 UI/L; hs-CRP, 0.5 mg/dL. eGFR was assessed using the chronic kidney disease epidemiology collaboration (CKD-EPI) equation [15]; and VTE risk was estimated using the Padua score [16].…”
Section: Patients and Calculationsmentioning
confidence: 99%
“…The coronavirus disease 19 (COVID-19) pandemic has been an ongoing global emergency since the first case was detected in December 2019; accordingly, from 1 January 2020 to 31 December 2021, a total of 5.94 million COVID-19 deaths were reported worldwide [ 1 ] and seroprevalence studies showed that the real prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection could be 10 times more than recorded [ 2 , 3 ]. This led many governments around the world to modify population lifestyle through social distancing and lockdown measures to limit the spread of infection.…”
Section: Introductionmentioning
confidence: 99%